2021
DOI: 10.1002/lio2.670
|View full text |Cite
|
Sign up to set email alerts
|

Does intraoperative ciprofloxacin‐soaked gelfoam have adverse effects on graft success rate? A randomized, double‐blind controlled trial

Abstract: Objectives: The aim of this study was to evaluate whether intraoperative ciprofloxacin-soaked gelfoam is safe in tympanoplasty or not.Method: In this randomized, double-blind controlled clinical study, we included 100 patients between 18 and 60 years old, having perforation ≥50% of the tympanic membrane and dry ear for at least 2 months who were a candidate for underlay tympanoplasty via postauricular approach. We used ciprofloxacin soaked gelfoam in the case group and betamethasone soaked gelfoam in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In previous studies [7,8], non-absorbable packs were found to be very uncomfortable for patients postoperatively and painful to remove. To overcome the disadvantages associated with nonabsorbable packs, a variety of biodegradable ear packs have been developed [9][10][11]. Absorbable ear packing materials are effective as they accelerate the overall healing process and improve postoperative hearing [3].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies [7,8], non-absorbable packs were found to be very uncomfortable for patients postoperatively and painful to remove. To overcome the disadvantages associated with nonabsorbable packs, a variety of biodegradable ear packs have been developed [9][10][11]. Absorbable ear packing materials are effective as they accelerate the overall healing process and improve postoperative hearing [3].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of COM surgery is the reconstruction of tympanic membrane (TM) perforation and the establishment of a sound‐conducting structure in a well‐aerated middle ear. 1 , 2 , 3 Surgical technique is an important factor in the graft success rate. 4 , 5 Different materials and techniques have been developed for tympanoplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic otitis media (COM) surgery is common all over the world, especially in developing countries. The aim of COM surgery is the reconstruction of tympanic membrane (TM) perforation and the establishment of a sound‐conducting structure in a well‐aerated middle ear 1–3 . Surgical technique is an important factor in the graft success rate 4,5 .…”
Section: Introductionmentioning
confidence: 99%